Gender identity in Peru: the case of trans children and adolescents. The difficult way to reveal the invisible - Plácido Vilcachagua, Alex F. (2020)
The process that is taking place in Peru is shown, for the recognition of the right to gender identity. Its beginning, which shows total lack of protection, presents a constant intolerance, manifested through acts of violence against LGBTI people; without the State investigating and sanctioning such violations. This has been evidenced by the judgment of the Inter-American Court of Human Rights in the case of Azul Rojas Marín and another v. Peru; situation to which trans children and adolescents are no stranger. Now, the actions of the Peruvian State are directedtowards showing the invisible, along a tortuous path that aims to get out of lack of protection and reach full recognition of gender identity as a right.